Digital Therapeutics: A New Frontier in Treatment - Uppuluri, Vijitha (International Journal of Health Sciences, 2025)
Purpose: This study aims to explore the evolution, applications, and potential of Digital Therapeutics (DTx) in transforming modern healthcare, particularly in managing chronic diseases, mental health, and behavioral conditions. It seeks to analyze how DTx bridges the gap between traditional medical practices and the growing digital innovation landscape in healthcare. Methodology: The research adopts a structured analytical approach involving the examination of current DTx applications, synthesis of clinical trial results, and development of a conceptual framework for effective DTx implementation. It evaluates mechanisms of action, regulatory standards, clinical validations, and technological integrations such as artificial intelligence (AI), machine learning (ML), and big data analytics. Findings: The study highlights significant improvements in patient outcomes, particularly in the management of diabetes, cognitive behavioral therapy (CBT), and substance abuse through DTx solutions. It identifies key benefits including better patient adherence, enhanced scalability, and improved cost-effectiveness when compared to traditional treatments. However, it also recognizes persistent challenges such as regulatory ambiguity, data privacy concerns, limited integration with existing healthcare infrastructure, and variable patient engagement. Unique Contribution to Theory, Practice, and Policy (Recommendations): This paper contributes to theoretical understanding by framing a conceptual model for DTx implementation and adoption. Practically, it emphasizes the value of AI-driven personalization in therapy and the importance of real-time data tracking in patient care. Policy-wise, it calls for clearer regulatory pathways, robust data governance frameworks, and cross-sector collaboration among clinicians, regulators, technologists, and patients. The research underscores the necessity of a unified ecosystem to fully realize the potential of digital therapeutics in mainstream healthcare.